Interaction of fumigaclavine C with High Mobility Group Box 1 protein (HMGB1) and its DNA complex: A computational approach. (December 2020) - Bailly, Christian; Vergoten, Gérard
Graphical abstract: Highlights: The fungal alkaloid fumigaclavine C (Fm-C) represses the production of inflammatory cytokines in cells. Fm-C inhibits the expression and functions of the alarmin protein HMGB1. The interaction of Fm-C and derivatives, with HMGB1 and HMGB1-DNA complex was investigated by molecular modeling. Fm-C can form stable complexes with HMGB1 in its free and DNA-bound forms. Fm-C is a better HMGB1 binder than Fm-A and Fm-B, or the structurally related drug LSD. Abstract: The fumigaclavines represent a small group of clavine-type alkaloids produced by the pathogenic fungus Aspergillus fumigatus . The leading compound in the family is fumigaclavine C (Fm-C) endowed with potent anti-inflammatory properties. Fm-C represses the production of several inflammatory cytokines in cells via a mechanism implicating a reduced nucleo-cytoplasmic transport and extracellular export of the alarmin protein HMGB1, through a direct drug-protein interaction, and a down-regulation of HMGB1 expression. We have investigated the interaction of Fm-C with HMGB1 using two complementary forms of the HMG-box protein, in its free and DNA-bound configurations, using molecular modeling. We identified up to six potential binding sites for Fm-C in the vicinity of the B-box of HMGB1, with the site designated Lys-103 being the most favored and maintained when the protein is bound to a 16-base pair DNA oligonucleotide. Structure-binding relationships have been explored through the comparison of the HMGB1-binding properties of fumigaclavines A, B and C, and the related alkaloid lysergic acid diethylamide (LSD). Both the C-9 acetyl group and C-2 dimethylallyl side chain of Fm-C contribute importantly to the protein interaction. LSD appears also to form stable complexes with free HMGB1. According to the calculated empirical energies of interaction (ΔE), the compounds rank in the order: Fm-C ∼ LSD < Fm-A < Fm-B, for binding to HMGB1. The study helps to better comprehend the mechanism of action of Fm-C, and its anti-inflammatory and anticancer properties.